Pendidikan Multikultural dalam Menjaga Kerukunan Umat Beragama dan Kebinekaan Indonesia di SMA Selamat Pagi Indonesia Kota Batu (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia is one of the largest multicultural nations in the world. This is in accordance with social and cultural conditions, as well as the location of the region which is so diverse and very wide, and consists of various ethnicities, cultures, races, religions and languages. With a country that is guided by Bhineka Tunggal Ika and Pancasila, it requires education that has various functions, whose main purpose is self, social, state, nation and even world intelligence. Multicultural education is an educational reform, and an educational process whose goal is to prioritize changing the structure of educational institutions so that students with disabilities, and students from diverse races, ethnicities, and cultures have equal opportunities to obtain knowledge and guidance without discrimination. This research uses a case study approach and the type of research is qualitative. Meanwhile, the data analysis technique used is domain analysis to obtain an overview of the research subject, as well as taxonomic analysis to describe the data in more detail, the data obtained from interviews, observation and documentation. Based on the results of the study, it can be concluded that there is a concept of multicultural education made by the school in accordance with the main objectives of the foundation, which is multicultural, and the implementation of multicultural education in the curriculum and learning inside and outside the school that runs very well. The attitude of being able to understand, appreciate, maintain and accept is reflected in the daily behavior of students, both at school and outside school. That is the support in maintaining religious harmony and Indonesian diversity.